A sequence of problems on semigroups - Neuberger, J. W. (John W.) 1934- (Problem Books in Mathematics, 2011)
A Sequence of Problems on Semigroups consists of an arrangement of problems which are designed to develop a variety of aspects to understanding the area of one-parameter semigroups of operators. Written in the Socratic/Moore method, this is a problem book with neither the proofs nor the answers presented. To get the most out of the content requires high motivation to work out the exercises. However, the reader is given the opportunity to discover important developments of the subject and to quickly arrive at the point of independent research. Many of the problems are not found easily in other books and they vary in level of difficulty. A few open research questions are also presented. The compactness of the volume and the reputation of the author lends this concise set of problems to be a 'classic' in the making. This text is highly recommended for use as supplementary material for three graduate level courses.